2004
DOI: 10.1111/j.1467-9310.2004.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the technology‐push of a discontinuous innovation in practice

Abstract: The hydraulic power generation business is usually faced with continuous innovation, meaning that progress is rather made in small than in large steps. Nevertheless, there are currently some examples of discontinuous innovation, the Powerformer‐technology being one of them. The implying difficulties for successful innovation are internal communication and linking the technology to the most suitable markets. In order to proficiently push the Powerformer‐technology onto the markets, an appropriate procedure is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…These complex decisions suggest the need for a strategy formulation framework, of which the best known include Porter's (1985) competitive analysis, or for innovation focus, the use of SWOT and technology choices for promoting discontinuous innovation (Meyhack et al, 2002;Schwery and Raurich, 2004). However, few frameworks specific to OI exist, and notably Witzeman et al (2006) suggest a process for strategic OI planning delineated by four thoughts: (1) 'Want' -What external resource(s) does the firm want to access to meet its strategic intent?…”
Section: Oi Strategymentioning
confidence: 99%
“…These complex decisions suggest the need for a strategy formulation framework, of which the best known include Porter's (1985) competitive analysis, or for innovation focus, the use of SWOT and technology choices for promoting discontinuous innovation (Meyhack et al, 2002;Schwery and Raurich, 2004). However, few frameworks specific to OI exist, and notably Witzeman et al (2006) suggest a process for strategic OI planning delineated by four thoughts: (1) 'Want' -What external resource(s) does the firm want to access to meet its strategic intent?…”
Section: Oi Strategymentioning
confidence: 99%
“…They found four forces emerged that have impacted the industry, yet have resulted in few modified strategies. Schwery and Raurich (2004) studied new technologies within the hydraulic power generation business. The use of a SWOT analysis revealed that the technology push was appropriate in specified market segments.…”
Section: Marketing and Social Mediamentioning
confidence: 99%
“…Similar results were found in telecommunications across the European Union (Blackman and Forge, 2008). Schwery and Raurich (2004) used the SWOT analysis to assess new technologies within the hydraulic power generation business. They reported the technology push was found in specified market segments.…”
Section: Industrymentioning
confidence: 99%